Training of Human Resources for Health in the Republic of Guinea-Bissau: Evolution of Structures and Processes in a Fragile State - Sá-Guerreiro, Cátia (2018)
Introduction: In the context of fragility that characterizes the Republic of Guinea-Bissau, there is an absence of effective management of human resources for Health, which begs reflection regarding training that is provided. The purpose of this study was to analyse the training of human resources for Health in the Republic of Guinea-Bissau since 1974, placing it in the national context and relating the analysis to the situation described for Fragile States.Material and Methods: Using the content analysis of the results of semi-structured interviews, focus group and documentary analysis, we analysed the training offer on human resources for Health in two pillars - at the level of the structures / training institutions; and at the level of processes. The consideration of the context in which it takes place allowed for an integrated analysis in the reality experienced by Fragile States.Results: We synthesize the historical steps of the establishment of human resources for Health, describing the structures and their procedures, concretely of the public entities like the National School of Health and the Faculty of Medicine, as well as of the private entities that proliferate in the country.Discussion: The country reflects the problems that have been identified for the African Region, and for Fragile States in particular, namely: weak health leadership / governance; limitation in the implementation of the planned training strategies; inadequate human resources training capacity; total / partial dependence on training funding, proliferation of private, unofficially recognized training providers.Conclusion: The models that emerge as a response to the fragility in this area partially allow to respond to the training needs of the country but neglect the quality and perpetuate dependencies, aggravating the weaknesses of the State and of the public sector.